Caracterização geomecânica de mármores da mina Calcário Mudador - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Representing 7% of national GDP (IBGE.2017), Brazil's civil construction sector is one of the most important in the national economy, with a significant number of more than 215 thousand companies active in the area. The high level of requirements related to the quality of materials used in construction activities requires increasingly sophisticated analyzes and monitoring for the certification of the quality of the materials involved in the processes. The technological control of aggregates consists of a relatively new method, where the rock aggregates used in the production of materials are submitted to a series of analyzes and tests. The objectives of characterizing and determining chemical and physical parameters are fundamental for determining the potential of use of each of the aggregates. Problems related to the quality of rock aggregates can generate unforeseen and unnecessary costs in the process of producing materials considered as "pillars" of civil construction such as cement, crushed stone and asphalt concrete. Such problems can be avoided by using methods that monitor the quality of these materials so that they are used correctly in their respective activities. The Limestone Mudador quarry located in the municipality of Caçapava do Sul-RS was chosen to carry out the work by having two types of marble, which differ both textural and compositional. When selecting quarry samples, they are subjected to chemical analysis, macro and microscopic petrography and geotechnical tests whose results, based on norms, determine characteristics such as shape, alterability, lamellarity, which characterize the physical parameters of the aggregates, the that allows the allocation or restriction of the potential of their use for certain projects.
Keywords: Agregado; Petrografia; Geotecnia; Aggregates; Petrography; Geotechnical; CNPQ::CIENCIAS EXATAS E DA TERRA